2020
DOI: 10.1111/ppl.13167
|View full text |Cite
|
Sign up to set email alerts
|

Optimising the foliar uptake of zinc oxide nanoparticles: Do leaf surface properties and particle coating affect absorption?

Abstract: Foliar absorption of zinc (Zn) is limited by several barriers, the first of which is the leaf cuticle. In this study, we investigated the absorption of Zn from Zn oxide nanoparticles (ZnO-NPs) in wheat (Triticum aestivum cv Gladius) and sunflower (Helianthus annuus cv Hyoleic 41) to determine the importance of NP surface coating for Zn absorption. Fourier transform infrared (FTIR) spectroscopy showed a higher polysaccharide content in the wheat cuticle than sunflower, indicated by a more pronounced glycosidic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 47 publications
6
18
0
Order By: Relevance
“…This protective effect and process could have occurred under both sets of conditions in our experiment (growth chamber and field). This effect was observed recently for Zn nanoparticles in two different types of leaf, wheat and sunflower, for which the authors indicated that coating may facilitate particle adhesion to leaves, providing a long-term source of uptake of Zn ions into leaves [52]. Furthermore, this process probably did not occur with the Fe vesicles since some elements (such as Fe), due to their chemical properties, can compete for water, causing dehydration of the pore and cutting the flow between the two sides of the structure [53].…”
Section: Discussionsupporting
confidence: 58%
“…This protective effect and process could have occurred under both sets of conditions in our experiment (growth chamber and field). This effect was observed recently for Zn nanoparticles in two different types of leaf, wheat and sunflower, for which the authors indicated that coating may facilitate particle adhesion to leaves, providing a long-term source of uptake of Zn ions into leaves [52]. Furthermore, this process probably did not occur with the Fe vesicles since some elements (such as Fe), due to their chemical properties, can compete for water, causing dehydration of the pore and cutting the flow between the two sides of the structure [53].…”
Section: Discussionsupporting
confidence: 58%
“…The Zn accumulated in leaves from foliar supply of ZnO NFs can be efficiently utilized in metabolic processes of plants [ 80 , 81 ]. This accumulation can be attributed to the direct absorption of ZnO NPs by the leaf cuticles of wheat plants and their movement across the leaf epidermis via stomata, their release in apoplast and then adhesion to the mesophyll cells irrespective of the particle coating [ 54 , 82 ].…”
Section: Wheat Micronutrients Nanobiofortification Via Foliar Fertilizationmentioning
confidence: 99%
“…In another short-term exposure study (24 h), wheat leaves exposed to zinc salts containing 0.05 wt% of Tween20 resulted in about six times greater Zn content in wheat leaves than the ZnO NMs-Tween20 foliar exposure. However, no significantly Zn content differences were found among ZnO NMs-Tween20 suspensions with different coatings [29]. The authors proposed that ionic adsorption was likely the dominant mechanism for passing through the cuticular pathway.…”
Section: Introductionmentioning
confidence: 96%
“…Many factors can affect the effectiveness of NMs foliar application processes, including NM properties (e.g., size [28][29][30], concentration [31][32][33], zeta potential [30], response duration [31], and coating [29,30]), leaf surface characteristics (e.g., wax thickness, pores, trichomes, and epidermis maturity) [34,35], NM uptake pathways (i.e., stomata [32,36,37] vs. cuticle [29,30]), and environmental factors [2,[27][28][29]. For example, Avellan et al, (2019) investigated the effects of Au NMs sizes and coatings for wheat foliar exposure without the assistance of surfactants [30].…”
Section: Introductionmentioning
confidence: 99%